An echocardiographic study of right and left ventricular adaptation to physical exercise in elite female orienteers - Henriksen, E.; Landelius, J.; Kangro, T.; Jonason, T.; Hedberg, P.; Wesslen, L.; Rosander, C. N.; Rolf, C.; Ringqvist, I.; Friman, G. (European Heart Journal, 1999)
BACKGROUND: A considerable body of echocardiographic studies has described how athletic training induces morphological adaptation of the left ventricle in male endurance athletes, but only a few studies have described left ventricular adaptation in female endurance athletes. In contrast to changes in the left ventricle far less attention has been directed towards right ventricular changes due to extensive physical exercise. The purpose of this study was to obtain normal values and to determine if there are any differences in right and left ventricular cavity and wall dimensions between female orienteers and females with a mainly sedentary lifestyle. METHODS: Echocardiography was performed in 42 highly trained elite female orienteers and 32 healthy female students with a predominantly sedentary lifestyle. The 74 females had no history of cardiac disease, a normal electrocardiogram and showed no echocardiographic abnormalities. M-mode and two-dimensional measurements of the right and left ventricular cavity and wall were obtained in elite orienteers and sedentary females. For the right ventricle and wall, multiple cross-sections were used and measurements were obtained from the right ventricular inflow and outflow tract. RESULTS: The left ventricular end-diastolic cavity dimension and the left ventricular wall thickness were significantly greater in the athletes compared with the sedentary controls. The right ventricular inflow tract measurements were all significantly greater in the orienteers compared with the controls but the right ventricular outflow tract measurements were comparable in the study groups. The right ventricular wall thickness, calculated as the mean of three different wall measurements was an average of 13% greater in the athletes compared with the sedentary controls. CONCLUSION: This study suggests symmetrical cardiac enlargement with a concomitant increase in both the right and left ventricular wall, probably reflecting the increased haemodynamic loading in the female athletes